Role of the principles of legal proceedings in the regulation of social relations - Пономаренко, Олександр Васильович; Ігнат, Антон Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In the article an author examines the issues about the features of the main principles of legal proceedings in process of it realization in the civil cases. The authors focus their attention on a detailed analysis of the principles of publicity, fairness, honesty and reasonableness in civil proceedings.